2020
DOI: 10.1093/hmg/ddaa041
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant in specificity protein 6 (SP6) is associated with amelogenesis imperfecta

Abstract: Amelogenesis is the process of enamel formation. For amelogenesis to proceed, the cells of the inner enamel epithelium (IEE) must first proliferate and then differentiate into the enamel-producing ameloblasts. Amelogenesis imperfecta (AI) is a heterogeneous group of genetic conditions that result in defective or absent tooth enamel. We identified a 2 bp variant c.817_818GC>AA in SP6, the gene encoding the SP6 transcription factor, in a Caucasian family with autosomal dominant hypoplastic AI. The resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Patients with high expression of KIF21B have been demonstrated to have a poorer prognosis in hepatocellular carcinoma ( Zhao et al, 2020 ) and non-small cell lung cancer ( Sun et al, 2020 ). SP6 is an important gene that regulates odontogenesis, belonging to a family of transcription factors that contain 3 classical zinc finger DNA-binding domains( Aurrekoetxea et al, 2016 ; Smith et al, 2020 ; Nakamura et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high expression of KIF21B have been demonstrated to have a poorer prognosis in hepatocellular carcinoma ( Zhao et al, 2020 ) and non-small cell lung cancer ( Sun et al, 2020 ). SP6 is an important gene that regulates odontogenesis, belonging to a family of transcription factors that contain 3 classical zinc finger DNA-binding domains( Aurrekoetxea et al, 2016 ; Smith et al, 2020 ; Nakamura et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of the several transcription factors, Msx2 and Sp6 constitute key players of amelogenesis. Both, Msx2 and Sp6 mouse mutants, exhibit enamel hypoplasia, while humans with AI carry mutations in the human homologues of MSX2 or SP6 genes (Satokata et al, 2000;Bei et al, 2004;Suda et al, 2006;Nakamura et al, 2008;Utami et al, 2011;Babajko et al, 2014;Smith et al, 2020). These similarities in function indicate that these two transcription factors may reside in the same developmental pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The Sp6 mutant mice among other phenotypes exhibit enamel hypoplasia (Nakamura et al, 2008;Utami et al, 2011). Recently, in a Caucasian family with autosomal dominant hypoplastic AI, a missense protein change, p.(Ala273Lys), is identified in SP6, the gene encoding the SP6 transcription factor (Smith et al, 2020). The authors have also "identified a potential SP6 binding motif in the AMBN proximal promoter sequence and showed that wildtype (WT) SP6 binds more strongly to it than the mutant protein, " further indicating the important role of Sp6 in amelogenesis (Smith et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated AI results from mutations in specific genes ( LAMB3, ENAM, AMBN, ITGB6, AMELX, KLK4, MMP20, WDR72, ODAPH, SLC24A4, FAM83H, DLX3, ARHGAP6, LAMA3, AMTN, ACPT, GPR68, RELT, SP6 ). 1 - 4 AI presents three subtypes: hypoplastic (type I), hypocalcified (type II), and hypomature (type III). 5 The prevalence of AI reaches 1/14 000 in the USA but to date, no existing epidemiologic study has been conducted in France.…”
Section: Introductionmentioning
confidence: 99%